(untitled) - International Rice Research Institute -- IRRI (Manila, Philippines, 1996)
Standard evaluation system for rice has been prepared to enabl rice scientists from around the world to speaka common language on evaluation of rice characters. This booklet has two major functions. The first is to expedite data collection, processing, and analysis of multi-environment trials. The second is to promote an interdisciplinary approach to rice improvement.
Keywords: Rice,Lúa